Mobile computing, applications, and services 4th International Conference, MobiCASE 2012, Seattle, WA, USA, October 11-12, 2012. revised selected papers - Mehta, Khanjan; Wong, Jennifer L. (Lecture notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the Fourth International Conference on Mobile Computing, Applications, and Services (MobiCASE 2012) held in Seattle, Washington, USA, in October 2012. The 18 revised full papers presented together with 9 revised poster papers were carefully reviewed and selected from 51 submissions. The conference papers are organized in five topical sections, covering mobile application development, multi-dimensional interactions, system support and architecture, mobile applications, and mobile services.